IMPLEMENTASI IDENTITAS KEPENDUDUKAN DIGITAL PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANDAR LAMPUNG - Kumara Dewi, Lies; Neysa Amallia; Henni Kusumastuti; Anida Nabila Fasya (LPPM STISIP IMAM BONJOL, 2026)
By using the descriptive method stages and using a qualitative approach, it is hoped that the dissemination of information about the IKD application will be conveyed comprehensively. The results of the study show that the implementation of the IKD application carried out by the Population and Civil Registration Office of Bandar Lampung City to make it easier for the public to process population data documents and implement online-based services has almost reached 15% of the target that should be achieved, namely 30%, this indicates that almost half of Bandar Lampung city residents have become active users of the IKD application. By using the IKD application, the community feels the benefits including the ease of making changes to population data, more efficiency and saving time because they do not need to queue for a long time. The implementation of the IKD application still faces technical and non-technical obstacles, including internet connectivity issues for IKD users, such as those whose smart devices cannot yet download the application, inadequate internet networks, and uneven public awareness campaigns, as well as some residents' lack of familiarity with how to use the application.